Catching My Anger: How Political Elites Create Angrier Citizens. (September 2022) - Stapleton, Carey E.; Dawkins, Ryan
Anger is a common feature in contemporary American politics. Through the process of affect linkage, we argue that one way the electorate becomes angrier about politics is by observing angry displays from political elites. Affect linkage occurs when a person's emotional state of mind changes to match the emotions displayed by someone else. Using an online experiment in which subjects are randomly exposed to an angry or unemotional debate between a Democrat and Republican running for Congress, we show that exposure to an angry in-party politician significantly increases the amount of anger, disgust, and outrage expressed by co-rank-and-file partisans. This increase in aversive emotions, moreover, increases the likelihood that citizens report the intention to vote, and this affect linkage effect is most pronounced in those who are most likely to stay home on election day: the weakest partisans. Interestingly, angry rhetoric by political elites does not have any effect on out-partisans, suggesting that anger via emotional contagion does not cross party lines.